'You can't Write that': The Challenges of Written Communication between Preschools and Schools. Issue 3 (September 2017) - Hopps-Wallis, Kathryn; Perry, Bob
RECENT REFORMS IN AUSTRALIA have brought an increasing expectation on early childhood educators to work together across settings at times of children's transition. In particular, the transition to school has been identified as an important time when educators are required to collaborate in order to support children, families and communities. Written forms of communication have been encouraged, and in some cases mandated, as a basis for transferring information about children from preschools to schools. The premise of such initiatives is that the information will enhance children's transitions by assisting schools to build on children's prior experiences. However, there has been little research into the practice of preschool–school communication including issues that impact on it. This article reports the challenges preschool and school educators identified in using written channels to transfer information between settings. The results indicate that written communication can be problematic. Several issues are identified that shape written communication practices and limit their effectiveness as a support for children and as a means of developing positive relationships between settings.